Action Video Game Training for Healthy Adults: A Meta-Analytic Study - Wang, Ping; Liu, Han-Hui; Zhu, Xing-Ting; Meng, Tian; Li, Hui-Jie; Zuo, Xi-Nian (Frontiers in Psychology, 2016)
Action video games have attracted increasing attention from both the public and from researchers. More and more studies found video game training improved a variety of cognitive functions. However, it remains controversial whether healthy adults can benefit from action video game training, and whether young and older adults benefit similarly from action video game training. In the present study, we aimed to quantitatively assess the action video game training effect on the cognitive ability of adults and to compare the training effects on young and older adults by conducting a meta-analysis on previous findings. We systematically searched video game training studies published between January 1986 and July 2015. Twenty studies were included in the present meta-analysis, for a total of 313 participants included in the training group and 323 participants in the control group. The results demonstrate that healthy adults achieve moderate benefit from action video game training in overall cognitive ability and moderate to small benefit in their abilities in specific cognitive domains. In contrast, young adults gain more benefits from action video game training than older adults in both overall cognition and specific cognitive domains. Age, education, and some methodological factors, such as the session duration, session number, total training duration, and control group type, modulated the training effects. These meta-analytic findings provide evidence that action video game training may serve as an efficient way to improve the cognitive performance of healthy adults. We also discussed several directions for future action video game training studies.